An Electromagnetic Signal Processor for Beam-forming a Wireless Mobile Sensor Station: Strengthening the Desired Signal and Nulling Main Interference - Hoole, P.R.P.; Abdul Rahim, L.M.; Julai, N.; Othman, Al-Hj; Hikmah Shabani, S.H.; Marzuki, Ade S.W.; Senthilkumar, K.S.; Pirapaharan, K.; Aravind, C.V.; Hoole, S.R.H. (International Journal of Control Theory and Applications, 2017)
This paper presents an electromagnetic signal processor of the electric field radiated by a three-element antenna array as a mobile station receiver which can increase power reception in the direction of the desired signal. As statistical, brute force estimation of the position of a wireless, mobile unit remains time consuming and memory wise heavy, as well as inaccurate, attempts are made to handle the changing environmental conditions surrounding a mobile unit, using estimators that function using more accurate, electromagnetic field models of the signal channel. Moreover, as reported in this paper, it is shown that analytically derived solutions of radiated electromagnetic fields may be used to increase the signal processing capability of the mobile unto to permit its transmission and reception maximized in a desired direction while cancelling out signals from undesired sources of interference. Number crunching systems consume time and memory, whereas the model based signal processor for beam steering proposed and investigated here is fast and light on memory usage. A two-element beam steered antenna presented before is extended to have a third antenna element placed in-between the two conventional elements, without any signal attenuation or phase shifting of this third element signal, results in a mobile unit that does simultaneous maximizing (towards the desired source) and minimizing (towards the undesired source or interferer) of the radiation signal strength.
Keywords: Beam forming; Smart Antenna; Adaptive Array; Wireless mobile sensor